Distributed Optimal Channel Access in Cognitive Radio Networks. - Mohapatra, Prasant (Computer (00189162), 2015)
This installment of Computer's series highlighting the work published in IEEE Computer Society journals comes from IEEE Transactions on Mobile Computing.